The Influence of Meal Experience on Revisit Intention at Nasi Bancakan Abah Barna, Bandung City - Handyastuti, Indriyani; Zahirah, Aulia; Fitriyani, Endah (Universitas Pendidikan Indonesia, 2021)
The main purpose of this study is to determine the effect of meal experience on revisit intention at Nasi Bancakan Abah Barna, Bandung City. Meal experience is a series of eating experiences that consumers feel from the time they enter the restaurant until they finish enjoying the food. The independent variable (X) is meal experience which has eight dimensions, namely food and drink, variety in menu choice, level of service, price and value for money, interior design, atmosphere and mood, location and accessibility and food and beverage service employee (Davis et al., 2018). While the dependent variable (Y) in this study is revisit intention with dimensions of likelihood to visit again, likelihood to recommend others, and likelihood to be the first choice for future visit (Ramukumba, 2018). This research uses quantitative and methods and explanatory survey. The results showed that simultaneously meal experience had a significant effect on revisit intention in Nasi Bancakan Abah Barna with a Fvalue of 6.498 Ftable of 2.04, therefore based on these results it is said that Fcount Ftable. Partial test results show that the dimensions of atmosphere and mood is obtained with tcount of 3.336 with Sig. 0.001 and the dimensions of location and accessibility is obtained with tcount of 2.486 with Sig. 0.015. These results show that the dimensions of atmosphere, mood, location, and accessibility on meal experience partially have a significant effect on revisit intention.